Gamification and CLIL: developing communication skills in L2 with the aid of digital tools in the bilingual context - Silva, Lucas A. (Anais Estendidos do Simpósio Brasileiro de Jogos e Entretenimento Digital (SBGames), 2022)
This paper describes the results of the project Game Development, an extracurricular subject designed for 11-12 year-old students in the bilingual context, at the Sphere International School, São José dos Campos, Brazil. Considering the relevance of CLIL to teaching EFL and the role that Gamification plays in terms of dynamizing the learning process of a foreign language - in this case, English -, it was possible to observe that both approaches encouraged the students to develop their communication skills and the digital literacy, in English, as part of the institution’s curriculum, in this project.